2008
DOI: 10.1093/plankt/fbn040
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of the mesozooplankton in the tropical Southwestern Atlantic

Abstract: Mesozooplankton species distribution and abundance were studied in the tropical Southwestern Atlantic, in neritic and oceanic regions off the state of Rio Grande do Norte, northeastern Brazil (38 to 68 S and 32830' to 35830' W). Samples were collected with a 120 mm mesh net towed horizontally at 40 stations along five transects in June 1986. A total of 151 taxa were identified. Copepoda (93 species) numerically dominated (78%) the community. The highest zooplankton abundance was recorded at a coastal station (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
27
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 21 publications
11
27
1
6
Order By: Relevance
“…Macpherson (2003) found results that suggested that the environmental or biological mechanisms regulating the latitudinal distribution of species have a greater global effect than the mechanisms regulating depth distribution. The chaetognath species collected around seamounts and islands off Northeastern Brazil were typical for tropical waters and showed little or no deviation from previous reports on studies in waters off Northeastern Brazil (Gusmão 1986, Cavalcanti and Larrazabal 2004, Neumann-Leitão et al 2008. The composition of the community as well, in terms of proportional abundance, was not unusual.…”
Section: Specific Compositionsupporting
confidence: 51%
“…Macpherson (2003) found results that suggested that the environmental or biological mechanisms regulating the latitudinal distribution of species have a greater global effect than the mechanisms regulating depth distribution. The chaetognath species collected around seamounts and islands off Northeastern Brazil were typical for tropical waters and showed little or no deviation from previous reports on studies in waters off Northeastern Brazil (Gusmão 1986, Cavalcanti and Larrazabal 2004, Neumann-Leitão et al 2008. The composition of the community as well, in terms of proportional abundance, was not unusual.…”
Section: Specific Compositionsupporting
confidence: 51%
“…The greater diversity of 398 dominant prey types in lower latitudes certainly follows the general pattern of increasing 399 diversity toward the equator (Hillebrand, 2004;Rombouts et al, 2009; van der Spoel and Pierrot-400 Bults, 1979); however, comparing the high diversity of dominant consumed prey types to the 401 observations that only a few of these groups are ever dominant in the environment (Hopcroft et 402 al., 1998;Llopiz et al, 2010;Neumann-Leitao et al, 2008) supports the likelihood that fish 403 larvae in lower latitudes, overall, exhibit a higher degree of prey selectivity. Unfortunately, very 404 few low-latitude studies quantitatively examined prey selectivity by comparing diets with prey 405 availability.…”
Section: Discussion 307mentioning
confidence: 82%
“…Subgroup 1 brought together numerically important calanoids in the epipelagic layer of coastal environments and tropical Atlantic Ocean, some of which, such as C. americana, are strong vertical migrants (Neumann-Leitão et al, 2008;Pessoa et al, 2014).…”
Section: Functional Features Of the Copepod Communitymentioning
confidence: 99%
“…In ocean, the holoplankton dominates numerically (Neumann-Leitão et al, 2008), and among all taxa, the copepods correspond to the most abundant (60 to 90% of the total abundance of zooplankton) and diverse group (Piontkovski et al, 2003). Furthermore, copepods play an important role in the functioning and maintenance of marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%